VD_FINDINFO Jug / 2023 / 268 vom 26. Januar 2023 - VD Tribunal cantonal (2023)
APPRÉCIATION DES PREUVES, COAUTEURDROIT PÉNAL, COMPLICITÉ, VOLDROIT PÉNAL, BRIGANDAGE | 139 ch. 3 al. 1 CP, 140 ch. 1 CP, 140 ch. 3 CP